Attorney-client privilege in criminal proceedings in the EU: need for common standards - Geraci, Marianna (ERA-Forum, 2025)
The right to attorney-client privilege is certainly recognised as a fundamental right in the context of European law. However, its implementation in practice does not seem to be protected by adequate safeguards. Starting from the case law of the European Court of Human Rights and the European Court of Justice, it would be possible to identify common standards to regulate this matter in criminal proceedings, since it is increasingly felt that the European Union needs to adopt (perhaps through a Directive) legislative measures to make the protection of the right to attorney-client privilege effective. The need for harmonisation of the rules was highlighted during the conference organised by ERA in October 2024 (reference is made to the conference “Protection of Attorney-Client Privilege in Criminal Proceedings in the EU”, held in Marbella on 3 and 4 October 2024), during which professors, prosecutors and jurists active in the field of criminal law from across Europe, discussed the protection of attorney-client privilege and argued for the importance of legislative action on the subject.